The Fourth Industrial Revolution: A New Ideology - Ian Moll (tripleC: Communication, Capitalism & Critique)
The hegemonic construal of the ‘Fourth Industrial Revolution’ portrays rapid technological developments as a bold, new industrial revolution. Since there is sparse evidence of any such revolution across the totality of social, political, cultural and economic institutions, locally and globally, the focus must turn to how this ideological frame functions to further the interests of social and economic elites worldwide. This article examines the way that Klaus Schwab, as the principal intellectual of the World Economic Forum and the interests it represents, has formulated and disseminated this ideology. The article argues that the ‘Fourth Industrial Revolution’ frame bolsters the contingent neoliberalism of the post-Washington consensus period, and therefore serves to obscure the continuing decline of the globalised world order with a ‘brave new world’ narrative.